KONSEP GUGATAN SEDERHANA SEBAGAI PRINSIF KEPASTIAN HUKUM - Nur Sa'adah (Ikatan Dosen Menulis, 2025)
In general, small claims are known as court lawsuits, which refer to the principle of simple, fast, and efficient justice for the settlement of legal matters between individuals or legal entities. In its regulations, cases that can be filed in a small claim are cases of breach of promise or unlawful acts, not related to the settlement of land rights, the value of the claim does not exceed five hundred million rupiah, and the settlement is not conducted through a special court as stipulated in the law. The lawsuit seeks to expand access to justice through regulations that have been made by the Supreme Court. In addition, it also introduces novelties in the process of resolving civil disputes in court. Activities related to the court that were previously imagined to be carried out only by advocates can now be carried out independently by the public. The public can experience firsthand how settlements are carried out; from registering themselves in court, registering a lawsuit, making payments, undergoing the conference process, to implementing the decision.